Association between influenza and the incidence rate of new‐onset type 1 diabetes in Japan. Issue 10 (3rd April 2021) - Nishioka, Yuichi; Noda, Tatsuya; Okada, Sadanori; Myojin, Tomoya; Kubo, Shinichiro; Higashino, Tsuneyuki; Nakajima, Hiroki; Sugiyama, Takehiro; Ishii, Hitoshi; Imamura, Tomoaki
ABSTRACT: Aim: This study aimed to determine whether there is an association between influenza and new‐onset type 1 diabetes. Materials and methods: This population‐based retrospective cohort study used data from the National Database of Health Insurance Claims and Specific Health Check‐ups of Japan. Influenza was defined based on drug prescriptions and the onset of type 1 diabetes was defined using specific medical codes indicating a diagnosis of type 1 diabetes. The incidence rate ratio of new‐onset type 1 diabetes within 180 days after an influenza diagnosis was calculated and it was compared with that at other times using Poisson regression and generalized estimating equations. Sensitivity analyses were performed to confirm the robustness of this finding. Results: The data of 10, 400 patients with new‐onset type 1 diabetes were analyzed, including 2, 196 (952 male 1, 244 female) patients diagnosed with influenza between 1 September 2014 and 31 August 2017. Although only patients with type 1 diabetes were included, adjusted analysis showed that individuals had a 1.3‐fold (95% confidence interval: 1.15–1.46) higher risk of developing type 1 diabetes in the first 180 days after influenza diagnosis than that at other times. Conclusions: In this Japanese population‐based cohort, the risk of new‐onset type 1 diabetes may increase after the diagnosis of influenza. These results, which must be confirmed in other populations, suggest that influenza may be a causal factor for new‐onset type 1 diabetes. The molecular mechanisms underlying the potential etiological relationship between influenza and type 1 diabetes should be elucidated. Abstract : In this Japanese population‐based cohort, the risk of new‐onset type 1 diabetes increased after being diagnosed with influenza. These results, which must be confirmed in other populations, suggest that influenza may be a causal factor for new‐onset type 1 diabetes. The molecular mechanisms underlying the potential etiological relationship between influenza and type 1 diabetes should be elucidated.